2001
DOI: 10.1038/sj.onc.1204576
|View full text |Cite
|
Sign up to set email alerts
|

Interchangeable binding of Bcl10 to TRAF2 and cIAPs regulates apoptosis signaling

Abstract: Bcl10 was identi®ed as a candidate gene responsible for low grade B cell lymphomas of mucosa-associated lymphoid tissue. Overexpression of Bcl10 in cultured cells was reported to promote apoptosis, however, the mechanism of regulation of apoptosis mediated by Bcl10 has not been demonstrated. In the present study, we analysed the apoptosis signaling pathway mediated by Bcl10, focusing on phosphorylation of Bcl10 and the dynamic interaction with its binding partners during apoptosis. Previously, we have demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…80 On the other hand, BIRC3/cIAP2 can bind and mediate the ubiquitination and degradation of Bcl10, an activator of NFκB identified as a candidate gene responsible for low grade B cell lymphomas of mucosaassociated lymphoid tissue. 99,100 Concerning BIRC4/XIAP-mediated NFκB activation, two different mechanisms, dependent and independent of TAK-1, have been observed as reported above (Fig. 2).…”
Section: Iaps: Regulators Of Cell Signalingmentioning
confidence: 81%
See 1 more Smart Citation
“…80 On the other hand, BIRC3/cIAP2 can bind and mediate the ubiquitination and degradation of Bcl10, an activator of NFκB identified as a candidate gene responsible for low grade B cell lymphomas of mucosaassociated lymphoid tissue. 99,100 Concerning BIRC4/XIAP-mediated NFκB activation, two different mechanisms, dependent and independent of TAK-1, have been observed as reported above (Fig. 2).…”
Section: Iaps: Regulators Of Cell Signalingmentioning
confidence: 81%
“…90 In contrast to most IAPs, BIRC6/Bruce (mouse homolog of human Apollon) deficiency in mice causes embryonic and neonatal lethality. 21,22,100 A characterization of a phenotype of mutant embryos at different stages of gestation shows no remarkable abnormalities and no enhanced apoptotis rate, but growth retardation and a delay in erythrocyte maturation. 21,22 These effects could be secondary to an impaired placenta development.…”
Section: Iaps: Essential For Development and Differentiationmentioning
confidence: 99%
“…[39][40] The phosphorylation status of Bcl10 can apparently modulate cell apoptosis, possibly by regulating the binding of Bcl10 to its molecular partners in the NF-kB/Rel-activating machinery. 41 Bcl10 expression in MALT lymphoma correlates with NF-kB/Rel nuclear levels. 42 Another MALT lymphoma translocation, t(11;18)(q21;q21), produces API2-MALT1, by fusing the gene for the human caspase-like molecule MLT1 to the caspase inhibitor -encoding gene iap2; 43 such a fusion activates NF-kB/ Rel factors.…”
mentioning
confidence: 99%
“…Hitherto, studies on Bcl10 have mostly been carried out on various types of lymphomas (44). In such tumors, Bcl10 is phosphorylated by several PKs, including Ca 2+ -calmodulin-dependent PKⅡ, AKT1, p38-MAPK, IκB kinase and PKC (21,30). Recently Kuo et al (45) demonstrated that the suppression of Bcl10 by siRNA hindered the growth of 4 otherwise untreated HCC cell lines (i.e., C33A, CaSki, HeLa and SiHa) through the NF-κB-dependent regulation of cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the enforced overexpression of wt Bcl10 protein weakly induces apoptosis and activates NF-κB in cells; yet, the expression of a Bcl10 mutant protein, in which the CARD domain is truncated, does not trigger apoptosis but activates NF-κB (26,28,29). Evidence to date suggests that the Bcl10 protein is involved in the autoproteolytic activation of pro-caspase-9 (28), in dissociating caspases from their inhibitors, cellular inhibitor of apoptosis proteins (cIAPs) (30), and in the formation of pro-apoptotic complexes with PKCζ at the NMs of HCC C4-I cells (20,31).…”
Section: Bcl10 Crucially Nucleates the Pro-apoptotic Complexes Comprimentioning
confidence: 99%